Prescribing Practices in the Outpatient Department in a Tertiary Care Teaching Hospital in Bangladesh - Afsan, Mohammad; Alam, Muhammad Mahbubul; Noor, Nushrat; Ahmed, AH Hamid (Update Dental College Journal, 2013)
A cross-sectional descriptive study was carried out among individuals attending the Out Patient Department (OPD) of Medicine, Paediatrics, Dermatology & Venerology, ENT, Orthopaedics and Gynaecology & Obstetrics from December 2011 to March 2012 in East-West Medical College Hospital, Dhaka, Bangladesh, to see the patterns of prescriptions using World Health Organization (WHO) core prescribing indicators and some additional indices. A total of 300 prescriptions were collected and analyzed by the 3rd year MBBS students in this study. The average number of drugs per encounter was 3.22 and 5.33% drugs were prescribed by generic name. Use of antibiotic (48.67% of encounters) was frequent, but injection use (6.67% of encounters) was within the recommendation of WHO. Only 26.09% drugs were prescribed from national essential drug list. Percentage of encounters with a NSAID, an anti-ulcerant, an antihistamine, a calcium preparation and a multivitamin & multimineral prescribed were 44.33%, 43.33%, 22.33%, 19.33% and 15.67% respectively. So, the findings from current study showed a trend towards inappropriate prescribing, particularly the over-prescribing of antibiotics and under-prescribing of generic drugs and also most of the drugs were prescribed out of national essential drug list. Hence, there would be needed for effective intervention program to encourage the physicians and healthcare providers in promoting more appropriate drug use. DOI: http://dx.doi.org/10.3329/updcj.v2i2.15483 Update Dent. Coll. j: 2012; 2 (2): 13-17